Assessment of myocardial work: a promising tool in obstructive and nonobstructive hypertrophic cardiomyopathy. (4th February 2022) - Garcia Bras, P; Aguiar Rosa, S; Moura Branco, L; Galrinho, A; Cardoso, I; Valentim Goncalves, A; Selas, M; Silva, F; Castelo, A; Ferreira, V; Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Myocardial work is a novel dynamic non‐invasive method for assessing myocardial deformation providing incremental information to left ventricular ejection fraction (LVEF) and strain imaging. The aim of this study was to assess left ventricular myocardial work in hypertrophic cardiomyopathy (HCM) and compare patients with obstructive HCM (oHCM) and nonobstructive HCM (nHCM). Methods: Prospective assessment of HCM patients' myocardial strain parameters with 2D speckle-tracking echocardiography, stratified according to LV segments (basal, midcavity and apical regions). Results were compared between oHCM and nHCM patients. Results: 83 patients with HCM, 60% male, 33% oHCM (with a LVOT gradient of 89 ± 60 mmHg). There was no significant difference between groups in mean age (56 ± 13 years vs. 55 ± 15 years, p = 0.719), LV mass index (186 ± 75 g/m2 vs. 158 ± 65 g/m2, p = 0.103), maximum wall thickness (21 ± 4 mm vs. 19 ± 5 mm, p = 0.425) or left ventricular ejection fraction (LVEF) (68 ± 8% vs. 67 ± 11%, p = 0.584). Regarding global work index (GWI) there was no significant difference between oHCM and nHCM (1206 ± 431 mmHg% vs. 1384 ± 437 mmHg%, p = 0.090), although oHCM patients had a significantly inferior GWI in the basal (921 ± 383 mmHg% vs. 1364 ± 419 mmHg%, p < 0.001) and midcavity (1049 ± 456 mmHg% vs. 1288 ± 492 mmHg%, p = 0.038) segments (Figure 1). No significant difference was noted in the apical segments (1680 ± 653 mmHg% vs. 1519 ± 770 mmHg%, p = 0.335). Myocardial work index in the basal segments showed inverse correlation with resting LVOT gradient (r=-0.242, p = 0.032) and maximum provoked LVOT gradient (r=-0.291, p = 0.010). Furthermore, patients with septal hypertrophy pattern showed significantly impaired basal myocardial work index compared with apical hypertrophy patients (1090 ± 428 mmHg% vs 1537 ± 389 mmHg%, p < 0.001). Global constructive work (GCW) (1443 ± 449 mmHg% vs. 1604 ± 426 mmHg%, p = 0.123) and global wasted work (GWW) (197 ± 140 mmHg% vs. 154 ± 107 mmHg%, p = 0.137) were not significantly different between groups. Global work efficiency (GWE) was significantly reduced in oHCM patients vs. nHCM (84.1 ± 7% vs. 88.3 ± 7.3%, p = 0.017), particularly in the basal (80.2 ± 11.2% vs. 88.3±.7.2%, p = 0.033) and midcavity segments (85.4 ± 9.2% vs. 90.0 ± 8.5%, p = 0.044) (Figure 2). No significant difference was noted in the apical segments (88.2 ± 9.9% vs. 87.0 ± 12%, p = 0.679). Myocardial work efficiency in the basal segments showed inverse correlation with resting LVOT gradient (r=-0.389, p = 0.002) and maximum provoked LVOT gradient (r=-0.446, p < 0.001). Moreover, patients with septal hypertrophy pattern showed significantly reduced basal myocardial work efficiency versus apical hypertrophy patients (83 ± 9% vs 92 ± 3%, p < 0.001). Conclusion: Myocardial work is a promising tool to evaluate myocardial function in patients with oHCM and nHCM. oHCM patients had a significantly inferior GWI and GWE particularly in the basal and midcavity segments versus nHCM patients.